Evaluating 3D-Printed Polylactic Acid (PLA)-Reinforced Materials: Mechanical Performance and Chemical Stability in Concrete Mediums - Hanna Csótár; Szabolcs Szalai; Dmytro Kurhan; Mykola Sysyn; Szabolcs Fischer (Applied Sciences)
The optimization and evaluation of 3D-printed polylactic acid (PLA) materials for reinforcing concrete elements present a promising avenue for advancing sustainable construction methods. This study addresses the challenges associated with PLA’s dual nature—biodegradable yet mechanically limited for long-term applications—while leveraging its potential to enhance concrete reinforcement. The research identifies gaps in understanding PLA’s mechanical and chemical behavior in alkaline environments, particularly its interactions with concrete matrices. To bridge this gap, four distinct PLA variants (high-impact PLA, engineering PLA, electrical ESD PLA, and gypsum PLA) and ABS (acrylonitrile butadiene styrene) were subjected to dissolution tests in NaOH solutions (pH 12 and 12.55) and mechanical evaluation under three-point bending using digital image correlation (DIC) technology. Test specimens were prepared using optimized 3D printing strategies to ensure structural consistency and were embedded in concrete beams to analyze their reinforcement potential. Force–displacement data and GOM ARAMIS measurements revealed significant differences in mechanical responses, with peak loads ranging from 0.812 kN (high-impact PLA) to 1.021 kN (electrical ESD PLA). Notably, electrical ESD PLA exhibited post-failure load-bearing capacity, highlighting its reinforcement capability. Chemical dissolution tests revealed material-specific degradation patterns, with high-impact and Gypsum PLA showing accelerated surface changes and precipitation phenomena. Observations indicated white crystalline precipitates, likely lime (calcium hydroxide—Ca(OH)2), residue from the dissolution tests (sodium hydroxide—NaOH), or material-derived residues formed on and near PLA elements, suggesting potential chemical interactions. These findings underline the critical role of material selection and optimization in achieving effective PLA–concrete integration. While PLA’s environmental sustainability aligns with industry goals, its structural reliability under long-term exposure remains a challenge. The study concludes that electrical ESD PLA demonstrates the highest potential for application in reinforced concrete, provided its chemical stability is managed, as its peak value (1.021 kN) showed 25.7% higher load-bearing capacity than high-impact PLA (0.812 kN) and did not lose any of its structural stability in the dissolution tests. This work advances the understanding of PLA as a sustainable alternative in construction, offering insights for future material innovations and applications.